(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Medical cannabis is now clearly defined as buds, cannabis concentrates or synthetic cannabinoids that are used for medicinal purposes. The main difference between medical marijuana and regular marijuana is the amount of tetrahydrocannabinol (THC), the main psychoactive component. In regular marijuana its content is 5%-35%, in medical marijuana - up to 1%The first person to use cannabis as an anaesthetic was the Chinese surgeon Hua To. He ground the plant into powder and mixed it with rice wine before surgeries, thus anaesthetising the patient. Today, cannabis is one of the 50 main herbs used in traditional Chinese medicine. Cannabis is used to treat rashes, wounds and ulcers, stimulate the nervous system, prescribed for flus, postpartum complications and poisoning. It is also used as an anthelmintic and diuretic. In ancient Egypt, medical marijuana is mentioned in several papyri at once. Texts show that the Egyptians used cannabis to relieve pain from haemorrhoids and to treat eye inflammation.